Trees and their effect on the productive stability of the grassland in a silvopastoral system - Ru?z, Tom?s E.; Febles, Gustavo; D?az, Humberto; Jord?n, Humberto (Cuban Journal of Agricultural Science, 2010)
An experiment was conducted for three years to study the effect of trees on the development of the associated grassland in a silvopastoral system. The tree legume Leucaena leucocephala cv. Peru was used, occupying 100 % of the grazing area, associated to Cynodon nlemfuensis, and a control of this grass without the inclusion of trees, fertilized or not, with 90 kg N/ha/year, through grazing in a random block design with four repetitions. The botanical composition of star grass, weeds and deserted spot , percentage of dead material and leaves were measured, as well as the number of depositions/m2 and biomass production of star grass. In the first and second year, after the beginning of the work, the percentage of star grass (81 and 52) was lower for the treatment where there was no effect of trees or the nitrogen fertilization (P < 0.05 and P < 0.01), while in the third year, the highest value (86 %) was reached when trees were planted (P < 0.001). The lowest weed value was always obtained with trees and did not differ only in the second year (13 vs 15 %) with the area fertilized with nitrogen (P < 0.01). The highest values of the deserted spot were always for the treatment without nitrogen fertilization or trees and did not differ in the first year (8 vs. 9 %) with the treatment fertilized with nitrogen (P < 0.05). In the rainy season, the treatment with trees did not differ from that with nitrogen fertilization, for the measurements biomass production of the pasture (2.70 vs 2.37 t/ha DM) and leaf percentage (34 vs. 31 %). However, it was the best for the rest of the measurements. In the dry season, the treatment with trees had the best behavior and did not differed only for the percentage of dead material (6 vs 12 %) receiving nitrogen fertilization (P < 0.05). In this study, the beneficial effects of trees in the grazing area were demonstrated consolidated in time through the increase of pastures, decrease of the uncovered area and higher biomass production, with higher leaf percentage and lower dead material. It was also confirmed that, when an improved pasture is not biologically or chemically fertilized, its productive characteristics are lost in time. Key words: shade, fertilization, grasses and leucaena.